Fostering positive experiences of group-based exercise classes after breast cancer: what do women have to say?. Issue 15 (16th July 2016) - Brunet, Jennifer; St-Aubin, Anik
Abstract: Purpose : The adverse side effects of current treatments for breast cancer highlight the need for rehabilitative programmes. Group-based exercise programmes have been found to be effective in reducing symptoms and treatment side effects and improving physical and psychological health in cancer survivors. To assist programme administrators and instructors in the ongoing design and delivery of optimal group-based exercise programmes, we conducted a longitudinal qualitative study to explore breast cancer survivors' perceptions of the instructor and the climate the instructor created within the context of a group-based exercise programme, and how this contributes to women's motivational experiences. Method : Seven women participating in an eight-week group-based exercise programme were interviewed at the start and end of the programme. Data were analysed using thematic analysis. Results : The instructor's attributes (energy, enthusiasm, approachability, knowledge, experience) and her focus on promoting self-improvement, personal progress, skill development and task mastery contributed to participants' positive experiences, which served to enhance their motivation to remain involved in the programme. Conclusions : Instructors play an essential role in creating a supportive climate and fostering positive experiences in group-based exercise programmes for breast cancer survivors. Hiring caring and knowledgeable instructors who are able to create a supportive climate may enhance breast cancer survivors' experiences in group-based exercise programmes and promote sustained participation. Implications for Rehabilitation: Promoting self-improvement, personal progress, skill development and task mastery can enhance breast cancer survivors' adherence to group-based exercise programmes, which can help mitigate the effects of cancer and its treatment. In addition to training leaders to run safe and effective programmes, hiring instructors who have high energy, and who are enthusiastic, approachable, knowledgeable and experienced can promote breast cancer survivors' adherence to group-based exercise programmes. Training in breast cancer management is required to allow instructors to understand the complexities of this disease and develop tailored exercise programmes. Future research needs to identify training techniques that can effectively promote exercise instructors' competence in working with breast cancer survivors.